2009
DOI: 10.1016/j.genhosppsych.2009.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Long-term psychiatric morbidities among SARS survivors

Abstract: The outbreak of SARS can be regarded as a mental health catastrophe. PTSD was the most prevalent long-term psychiatric condition, followed by depressive disorders. Our results highlight the need to enhance preparedness and competence of health care professionals in detecting and managing the psychological sequelae of future comparable infectious disease outbreaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

59
820
4
43

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 912 publications
(926 citation statements)
references
References 40 publications
59
820
4
43
Order By: Relevance
“…The outbreak of SARS-CoV in 2002 and 2003 in Guangdong Province,China, was regarded as a "mental health catastrophe"(Mak et al, 2009). The outbreak of SARS-CoV in 2002 and 2003 in Guangdong Province,China, was regarded as a "mental health catastrophe"(Mak et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The outbreak of SARS-CoV in 2002 and 2003 in Guangdong Province,China, was regarded as a "mental health catastrophe"(Mak et al, 2009). The outbreak of SARS-CoV in 2002 and 2003 in Guangdong Province,China, was regarded as a "mental health catastrophe"(Mak et al, 2009).…”
mentioning
confidence: 99%
“…, psychotherapy and pharmacotherapy interventions for the stressful impact of the 2019-nCoV outbreak should be given more attention in patients infected with 2019-nCoV, suspected persons, observed persons, and health care workers closely associated with the infected patients. Mak et al found that the cumulative incidence of psychiatric disorders was up to 58.9% (53/90) after the SARS-CoV outbreak(Mak et al, 2009). Mak et al found that the cumulative incidence of psychiatric disorders was up to 58.9% (53/90) after the SARS-CoV outbreak(Mak et al, 2009).…”
mentioning
confidence: 99%
“…Among survivors of many life threatening infectious diseases, psychiatric morbidities were observed (6)(7)(8)(9)12). Similar to CCHF, SARS is an infectious disease that has an acute course, but it is not chronic in process.…”
Section: Discussionmentioning
confidence: 99%
“…İzlenen PTSD oranları %10 ile %38 arasında değişmektedir. Hastaların büyük bir çoğunluğu da bu rahatsızlıklarından dolayı, doktora başvurup psikiyatrik yardım almamışlardır (7)(8)(9)(10)(11)(12).…”
Section: İrdelemeunclassified
“…Geçen yıllarda KKKA geçiren hastalarımızın bir kısmının PTSD tanısına ilerlemiş olma ihtimali mevcuttur. Literatürdeki diğer çalışmalarda da izlendiği gibi çoğu hastanın rahatsızlığı olması halinde bile doktora başvurmadığının bildirilmesi, bizim bölgemizde de şu anda psikiyatrik rahatsızlığı olan hastaların olabileceğini ve de psikiyatrik yardım almadıklarını düşündürmektedir (7)(8)(9)(10)(11)(12). Bu sonuçlara göre KKKA geçiren hastaların uzun dönemde psikiyatrik olarak değerlendirilmelerinin faydalı olabileceğini düşünmekteyiz.…”
Section: İrdelemeunclassified